2008
DOI: 10.1631/jzus.b0820009
|View full text |Cite
|
Sign up to set email alerts
|

Do rice water weevils and rice stem borers compete when sharing a host plant?

Abstract: Abstract:The rice water weevil (RWW) Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae) is an invasive insect pest of rice Oryza sativa L. in China. Little is known about the interactions of this weevil with indigenous herbivores. In the present study, adult feeding and population density of the weevil, injury level of striped stem borer Chilo suppressalis (Walker) (Lepidoptera: Pyralidae) and pink stem borer Sesamia inferens (Walker) (Lepidoptera: Noctuidae) to rice, as well as growth status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Both of these roots eventually initiate lateral roots (secondary and tertiary roots) on which water and nutrient absorbing root hairs are developed [ 13 ]. It has been reported that the number of roots in a plant is closely related to the tiller number per plant [ 14 , 15 ]. For example, Anderson-Taylor and Marshall [ 16 ] reported seminal and nodal roots of spring barley ( H. distichum L.) comprised of 40 and 60 percent, respectively of total roots and nodal root dry weight was correlated with primary tillers.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these roots eventually initiate lateral roots (secondary and tertiary roots) on which water and nutrient absorbing root hairs are developed [ 13 ]. It has been reported that the number of roots in a plant is closely related to the tiller number per plant [ 14 , 15 ]. For example, Anderson-Taylor and Marshall [ 16 ] reported seminal and nodal roots of spring barley ( H. distichum L.) comprised of 40 and 60 percent, respectively of total roots and nodal root dry weight was correlated with primary tillers.…”
Section: Introductionmentioning
confidence: 99%
“…The lower interspecific competition between FAW and stemborers than within stemborers could be explained by the fact that in contrast to stemborers, which only feed on leaves up to the third larval instar stage (even earlier stage for S. calamistis), FAW is a pure foliar feeder; thus, as on live plants, FAW larvae remained on the surface whereas borer larvae penetrated into the diet, where after the direct competition ended between FAW and stemborer larvae. Similarly, Shi et al [43] reported no evidence of interspecific competition between the rice water weevil, a leaf feeder and rice stemborers at the tillering stage in contrast to the booting or earlier developmental stages of rice.…”
Section: Discussionmentioning
confidence: 98%